Exposure of the alga Pseudokirchneriella subcapitata to environmentally relevant concentrations of the herbicide metolachlor: Impact on the redox homeostasis - Machado, Maria Manuela Dias (2021)
This study investigated the effect of the herbicide metolachlor (MET) on the redox homeostasis of the freshwater green alga Pseudokirchneriella subcapitata. At low MET concentrations (?40 ?g L?1), no effects on algal cells were detected. The exposure of P. subcapitata to 45235 ?g L?1 MET induced a significant increase of reactive oxygen species (ROS). The intracellular levels of ROS were particularly increased at high (115 and 235 ?g L?1) but environmentally relevant MET concentrations. The exposure of algal cells to 115 and 235 ?g L?1 MET originated a decrease in the levels of antioxidants molecules (reduced glutathione and carotenoids) as well as a reduction of the activity of scavenging enzymes (superoxide dismutase and catalase). These results suggest that antioxidant (non-enzymatic and enzymatic) defenses were affected by the excess of MET. As consequence of this imbalance (ROS overproduction and decline of the antioxidant system), ROS inflicted oxidative injury with lipid peroxidation and damage of cell membrane integrity. The results provide further insights about the toxic modes of action of MET on a non-target organism and emphasize the relevance of toxicological studies in the assessment of the impact of herbicides in freshwater environments.